Regulating ion transport and solvation chemistry in zwitterionic gel polymer electrolyte for high-performance quasi-solid-state batteries - Lu Nie; Xinru Wu; Haotian Qu; Runhua Gao; Xiao Xiao; Zhihong Piao; Gongxun Lu; Wenqiang Fang; Yanfei Zhu; Guangmin Zhou (Proceedings of the National Academy of Sciences, 2026)
Gel polymer electrolytes (GPEs) are promising electrolyte candidates for next-generation Li metal batteries (LMBs). However, the reverse migration of free anions causes uneven distribution of space charges and Li + flux, ultimately accelerating dendrite growth. Additionally, strong ion–solvent interactions lead to high Li + desolvation barriers and sluggish Li + transfer kinetics. To address these issues, we design a zwitterionic GPE, where the synergistic effects of zwitterionic groups promote Li-salt dissociation through ion–dipole interactions and simultaneously restrict anion migration, effectively suppressing space charge-induced dendrite growth. Moreover, the competitive coordination of zwitterions with Li + weakens the Li + -solvent interaction, accelerating interfacial Li + desolvation. Zwitterions in the inner solvation shell of Li + are preferentially reduced before the solvents, forming a conductive N- and S-rich inorganic interphase that enhances cycling stability. As a result, the zwitterionic GPE enables the Li||SPAN cells to deliver a high discharge capacity of 528.3 mAh g −1 at −20 °C, and achieve 79.6% capacity retention after 1,000 cycles. Besides, the Li||SPAN pouch cell, with an active mass loading of 10.5 mg cm −2 , delivers a high discharge capacity of 1.63 Ah and an impressive areal capacity of 16.3 mAh cm −2 . This work highlights the importance of regulating ion transport and ion–solvent chemistry for advanced quasi-solid-state LMBs.